A Balanced Approach to Project Management in Partnering Types of Contract: A Public Private Partnerships Framework - Mandiartha, Putu; Duffield, Colin (IEOM, 2016)
This paper investigates project management relationship employed in partnering types of contracts by investigating practices and gathering inputs from participants specifically involved in Public Private Partnership (PPP) projects in Australia. A detailed survey was conducted and the results revealed behavioral differences between project management of PPPs compared with the focus of more conventional projects where an adversarial approach is common rather than using a strategic approach in managing projects. This research indicates that, for the success of partnering type of projects, strategic aspects of project management play an important role and are equally important with traditional aspects of project management. Some of those critical areas of project management to balance the approach are identified and utilized in a new proposed project management framework. The proposed framework enhances the commonly utilized framework, developed by Project management Institute (PMI), by adding the strategic project management aspects into the architectural of the approach.